Gossypetin-7-0-β-D-Glucopyranoside, A Novel Flavonoid Glycoside from Impatiens Scabrida D.C. - Yadava, R.N.; Jain, Basanti (Asian Journal of Chemistry, 2010)
Phytochemical examination of Impatiens scabrida resulted in the isolation and identification of a novel flavonoid glycoside Gossypetin-7-0-β-D-glycopyranoside